Perceived social support and its relationship to Depression (A field study among a sample of first year Damascus university students) - ALzobe, Ahmad; كري لينا (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The present research aimed at revealing the nature of the relationship of perceived social support to Depression in Damascus university students. The researcher attempted to determine the level of perceived social support, and to disclose the nature of the differences between males and females in each of perceived social support and depression. The sample of the research consisted of (297) first year students in Damascus university, the number of male students was (149) and, the number of female students was (148). The tools of the research included perceived social support scale and a scale of depression, and were verified to ensure their validity and reliability by using appropriate scientific methods. This research came up with the following results: - There is a negative statistical significant relationship at the level of significance 0.01 between perceived social support and depression. -There are statistical significant differences at the level of significance 0.05 between males and females in perceived social support. -There are no statistical significant differences at the level of significance 0.05 between males and females in depression.